The academic library and the net gen student making the connections - Gibbons, Susan (Susan L.) 1970- (American Library Association, 2007)
As students embrace new Web 2.0 technologies like MySpace, YouTube, and RSS feeds, libraries also need to take charge. Helping you understand the integral role of technology in the social and academic lives of undergraduates, this guide maps potentially vibrant futures for academic libraries. It also helps you understand hot technologies.